A bionic wearable strain sensor device and a preparation method and application thereof
Patent Information
- Application Number
- CN202611218607.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]发明目的:本发明的目的是解决现有传感器件刚性不贴合、导电性与力学性能难以兼顾、易脱水收缩、信号易漂移以及生物基含量低的问题,提供了一种仿生可穿戴应变传感器件及其制备方法与应用
[0021]有益效果:1. 本发明的传感器件以离子迁移作为信号传导媒介,与人体皮肤及神经系统通过离子迁移传递感知信息的机制相似,属于仿生离子导电型应变传感;同时仿生离子导电水凝胶传感层具有与人体表皮相近的低弹性模量,可与皮肤共形贴附、适应皮肤的动态变化,实现舒适、稳定、灵敏的仿生穿戴式感知。
Smart Images

Figure CN122961279A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible sensing and wearable electronic materials technology, and relates to a biomimetic wearable strain sensor device, its preparation method and application. Background Technology
[0002] The core of human-computer interaction lies in converting human movement, posture, and physiological activities into recognizable and transmittable electrical signals in real time. Among various flexible sensing materials, ion-conductive hydrogels use ion migration as a signal transmission medium, which is highly similar to the ion-type sensing mechanism of human skin and nervous system. They also have high tensile strength, a mechanical modulus similar to that of skin, and good conformal adhesion, making them an ideal material for constructing biomimetic wearable strain sensor devices.
[0003] However, existing sensor devices still have many shortcomings when facing real human-computer interaction applications. Traditional strain sensors mostly use rigid materials such as metals and semiconductors, which are difficult to conform to the skin, have poor wearing comfort, and are prone to failure under large deformations. Existing conductive hydrogels are mostly based on fully synthetic polymers, with low bio-based content and difficult degradation after disposal. At the same time, it is often difficult to balance conductivity and mechanical properties in such hydrogels. Conductive fillers or electrolyte salts introduced to improve conductivity tend to agglomerate, causing stress concentration and reducing tensile strength, while high chemical cross-linking sacrifices toughness. Moreover, commonly used chemical cross-linking agents such as glutaraldehyde are toxic, and systems that rely on soluble salts for conductivity are also prone to salt ion diffusion and conductivity decay, making it difficult to meet the requirements of signal stability and repeatability for human-computer interaction. Summary of the Invention
[0004] Purpose of the invention: The purpose of this invention is to solve the problems of existing sensor devices, such as rigidity and non-fitting, difficulty in balancing conductivity and mechanical properties, easy dehydration and shrinkage, easy signal drift, and low bio-based content, and to provide a biomimetic wearable strain sensor device, its preparation method and application.
[0005] Technical solution: The present invention provides a biomimetic wearable strain sensor, comprising a biomimetic ion-conductive hydrogel sensing layer, electrodes disposed at both ends of the biomimetic ion-conductive hydrogel sensing layer, and an elastomer encapsulation layer covering the outside of the biomimetic ion-conductive hydrogel sensing layer and the electrodes; the raw materials of the biomimetic ion-conductive sensing layer include polyvinyl alcohol, amylopectin, zinc sulfate and water, and the biomimetic ion-conductive hydrogel sensing layer is prepared by ion crosslinking of a hydrogel formed by freeze-thaw cycles of polyvinyl alcohol, amylopectin and water into a zinc sulfate solution.
[0006] Furthermore, in the biomimetic ion-conductive hydrogel sensing layer, the mass ratio of polyvinyl alcohol to amylopectin is (3~6):(1~3); the total mass of polyvinyl alcohol and amylopectin accounts for 10%~12.5% of the total mass of polyvinyl alcohol, amylopectin and water.
[0007] Further, the zinc sulfate solution is characterized by having a concentration of 0.5~2 mol / L.
[0008] Furthermore, the degree of polymerization of the polyvinyl alcohol is 1700-1800, and the degree of hydrolysis is 99%; the amylopectin is one or more of corn amylopectin, potato amylopectin, wheat amylopectin, and cassava amylopectin.
[0009] Furthermore, the electrode is a copper electrode, copper foil, or silver wire connected to both ends of the biomimetic ion-conductive hydrogel sensing layer via conductive silver paste.
[0010] Furthermore, the elastomeric encapsulation layer is a polydimethylsiloxane film, VHB tape, or Ecoflex silicone rubber film.
[0011] Another aspect of the present invention is to provide a method for fabricating the above-mentioned biomimetic wearable strain sensor device, comprising the following steps:
[0012] S1. Add polyvinyl alcohol to water, allow it to swell at room temperature, and then heat and stir at 90~95℃ until completely dissolved to obtain a polyvinyl alcohol solution;
[0013] S2. Take another branched starch and add it to water, then stir and disperse it at 60°C to obtain a branched starch dispersion;
[0014] S3. The amylopectin dispersion is mixed with the polyvinyl alcohol solution, and stirred at 90~95°C to fully gelatinize the amylopectin and mix it evenly to obtain a polyvinyl alcohol / amylopectin mixed solution;
[0015] S4. After degassing the mixed solution, pour it into a polytetrafluoroethylene mold, freeze it at -20°C, thaw it at 20~25°C, and repeat the cycle 2~3 times to obtain polyvinyl alcohol / branched starch hydrogel.
[0016] S5. The polyvinyl alcohol / branched starch hydrogel is immersed in zinc sulfate solution for ionic crosslinking, and then washed to obtain a biomimetic ion-conductive hydrogel as a sensing layer.
[0017] S6. Electrodes are connected to both ends of the sensing layer using conductive silver paste, and then encapsulated with an elastomer layer to obtain the biomimetic wearable strain sensor device for human-computer interaction applications.
[0018] Further, in step S1, the swelling time is 0.5~2 h, the heating and stirring speed is 200~400 r / min, and the time is 2~3 h; in step S2, the stirring and dispersing time is 1~2 h; and in step S3, the gelatinization time is 1~1.5 h.
[0019] Further, in step S4, the degassing is performed under vacuum at 80-85°C for 30-40 min; the freezing time is 12-15 h, and the thawing time is 8-12 h; in step S5, the soaking temperature is 20-25°C, and the soaking time is 48-72 h; and the washing is performed by rinsing with deionized water 2-4 times.
[0020] Another aspect of the present invention is to provide the application of the above-mentioned bionic wearable strain sensor in human-computer interaction, wherein the bionic wearable strain sensor is attached to the surface of human joints, skin or muscles to collect human motion signals or physiological signals, and the signals are used for gesture recognition, finger bending monitoring, writing recognition, pulse monitoring, swallowing monitoring, remote robotic arm control or Morse code communication.
[0021] Beneficial effects: 1. The sensor device of the present invention uses ion migration as a signal transmission medium, which is similar to the mechanism by which human skin and nervous system transmit sensory information through ion migration. It belongs to the biomimetic ion-conductive strain sensing. At the same time, the biomimetic ion-conductive hydrogel sensing layer has a low elastic modulus similar to that of human epidermis, which can conformally adhere to the skin and adapt to the dynamic changes of the skin, so as to achieve comfortable, stable and sensitive biomimetic wearable sensing.
[0022] 2. This invention uses polyvinyl alcohol (PVA) and amylopectin as the matrix. During freeze-thaw cycles, PVA forms microcrystalline regions through inter-chain hydrogen bonds, serving as physical cross-linking points. The gelatinized amylopectin molecular chains form abundant hydrogen bonds with the PVA molecular chains, constructing an interpenetrating network structure. The high hydroxyl content and branched structure of amylopectin facilitate the formation of a dense hydrogen bond network with PVA, significantly improving the energy dissipation capacity of the gel network. The biomimetic soft yet strong multi-scale cross-linking characteristics of biological tissue enable the hydrogel to maintain high tensile strength while achieving excellent strength and toughness.
[0023] 3. This invention uses zinc sulfate as both an ionic crosslinking agent and an ionic carrier, solving the problem of the mutual constraint between conductivity and mechanical properties. On one hand, zinc ions coordinate with the hydroxyl groups on the molecular chains of polyvinyl alcohol and amylopectin, serving as dynamic chemical crosslinking points to further enhance the strength and toughness of the gel network. On the other hand, dissociated zinc and sulfate ions migrate as charge carriers within the gel network, endowing the material with excellent ionic conductivity. Thus, the mechanical enhancement and conductivity improvement of the gel originate from the same component, eliminating the need for additional easily agglomerated conductive fillers, fundamentally overcoming the bottleneck of stress concentration and decreased tensile strength caused by uneven dispersion of conductive fillers.
[0024] 4. This invention employs room temperature thawing (20-25°C) instead of low-temperature thawing in the freeze-thaw process, effectively suppressing dehydration and shrinkage. Low-temperature thawing induces excessive secondary crystallization of polyvinyl alcohol molecular chains and exacerbates phase separation, causing significant water seepage and volume shrinkage after gel formation. This invention, through room temperature thawing, allows the molecular chains to rearrange in a more relaxed environment, enabling the water in the gel network to be retained in situ, thereby obtaining a hydrogel with uniform size and stable morphology. Combined with the elastomer encapsulation layer to suppress water evaporation, the sensor device of this invention exhibits baseline stability, low signal drift, and good repeatability during long-term use, meeting the stringent requirements for signal stability in human-computer interaction.
[0025] 5. The polyvinyl alcohol, amylopectin, and zinc sulfate used in this invention are all green, low-cost, and readily available raw materials. The preparation process does not use toxic chemical crosslinking agents such as glutaraldehyde, and the device has good biocompatibility and biodegradability. Moreover, the crosslinking and conductivity do not depend on the continuous presence of soluble salts, thus avoiding network damage and conductivity decay caused by the outward diffusion of salt ions.
[0026] 6. The biomimetic wearable strain sensor of the present invention has the advantages of high sensitivity, wide sensing range, fast response and excellent cycle stability. It can sense large movements such as finger bending and joint movement, as well as capture weak physiological signals such as pulse, swallowing and voice. It can also be combined with signal acquisition and wireless transmission modules to realize a variety of human-computer interaction functions such as gesture recognition, remote real-time control of robotic arms, handwriting recognition and Morse code communication. It is suitable for smart wearables, medical rehabilitation and remote control of robots. Attached Figure Description
[0027] Figure 1 The stress-strain curves of the biomimetic ion-conductive hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2 under different tensile strains are shown.
[0028] Figure 2 Pure PVA, PVA / amylated starch, and PVA / amylated starch / Zn 2+ A bar chart comparing the ionic conductivity of hydrogels under the same test conditions.
[0029] Figure 3 The toughness and dissipation energy of the biomimetic wearable strain sensor device of Embodiment 1 of the present invention after 50 tensile-recovery cycles at 30% strain;
[0030] Figure 4 The curves show the relative resistance change rate of the device in Example 1 under periodic light and heavy pressing conditions over time.
[0031] Figure 5 The curve shows the relative resistance change rate of the device in Example 1 under periodic deformation conditions over time.
[0032] Figure 6 This is a demonstration diagram showing how the device from Example 1 is used as a gesture input unit to drive a bionic robotic hand to present six representative gesture states. Detailed Implementation
[0033] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified. The degree of polymerization of polyvinyl alcohol is 1700-1800 and the degree of alcoholysis is 99%; corn amylopectin, zinc sulfate (ZnSO4), conductive silver paste, copper foil, and VHB tape are all commercially available products.
[0035] Example 1
[0036] A biomimetic wearable strain sensor for human-computer interaction applications is fabricated using the following steps:
[0037] S1. Weigh 3.75 g of polyvinyl alcohol and add it to 20 mL of deionized water. First, let it swell at room temperature for 1 h, and then heat and stir it in a 95℃ water bath at 300 r / min for 1.5 h until it is completely dissolved, to obtain a clear polyvinyl alcohol solution.
[0038] S2. While stirring polyvinyl alcohol, add 1.25 g of corn amylopectin to 20 mL of deionized water and stir at 60 °C to disperse evenly to obtain amylopectin dispersion (the mass ratio of polyvinyl alcohol to amylopectin is 3:1, and the total mass of the two is about 12.5 wt% of the system).
[0039] S3. Add the amylopectin dispersion to the polyvinyl alcohol solution above, and continue stirring at 95°C for 1 h to fully gelatinize the amylopectin and mix it evenly to obtain a polyvinyl alcohol / amylopectin mixed solution;
[0040] S4. The mixed solution was ultrasonically degassed at 60°C for 20 min, and while hot, it was injected into an 80 mm × 20 mm × 2 mm polytetrafluoroethylene mold. After sealing, it was frozen at -20°C for 12 h, and then thawed at room temperature at 25°C for 10 h. The above freezing-thawing process was repeated twice to obtain polyvinyl alcohol / branched starch hydrogel.
[0041] S5. The polyvinyl alcohol / branched starch hydrogel is immersed in 1 mol / L zinc sulfate solution and soaked at 25°C for 48 h to carry out ionic cross-linking. After being taken out, it is rinsed 3 times with deionized water and the surface moisture is absorbed with filter paper to obtain a biomimetic ion-conductive hydrogel.
[0042] S6. Cut the biomimetic ion-conductive hydrogel into strips of 30 mm × 10 mm × 2 mm, coat both ends with conductive silver paste and connect copper foil electrodes. After curing, wrap with VHB tape, lead out the electrodes and cover with another layer of VHB tape, seal the sides and retain the electrode contact ends to obtain a biomimetic wearable strain sensor for human-computer interaction applications.
[0043] Example 2
[0044] A biomimetic wearable strain sensor device is prepared in a manner that is basically the same as that in Example 1, except that the mass ratio of polyvinyl alcohol to corn amylopectin in S1~S3 is 4:1, that is, 4 g of polyvinyl alcohol and 1 g of corn amylopectin are weighed.
[0045] Example 3
[0046] A biomimetic wearable strain sensor device is prepared in a manner that is basically the same as in Example 1, except that the mass ratio of polyvinyl alcohol to corn amylopectin is 2:1, that is, about 3 g of polyvinyl alcohol and 1.5 g of corn amylopectin are weighed.
[0047] Example 4
[0048] A biomimetic wearable strain sensor device is prepared in a manner that is basically the same as that in Example 1, except that the number of freeze-thaw cycles in S4 is 1.
[0049] Example 5
[0050] A biomimetic wearable strain sensor device is prepared in a manner that is basically the same as in Example 1, except that the concentration of zinc sulfate solution in S5 is 0.5 mol / L.
[0051] Examples 2 through 5 can all form a complete biomimetic ion-conductive hydrogel sensing layer, which can be cut, connected by electrodes, and encapsulated with an elastomer to obtain a wearable strain sensor device. Wherein:
[0052] In Example 2, when the mass ratio of polyvinyl alcohol to corn amylopectin is 4:1, the resulting hydrogel can maintain an intact gel morphology; a higher proportion of polyvinyl alcohol can form a continuous physical cross-linked network, enabling the sensing layer to have morphological retention that meets the requirements of device assembly.
[0053] In Example 3, when the mass ratio of polyvinyl alcohol to corn amylopectin is 2:1, the hydrogen bonding between the gelatinized amylopectin and polyvinyl alcohol can still maintain the integrity of the composite network, and the resulting hydrogel has a flexible gel morphology that can be cut and encapsulated.
[0054] In Example 4, after one freeze-thaw cycle, the polyvinyl alcohol microcrystalline region and the hydrogen bonding of polyvinyl alcohol / branched starch can form a basic physical cross-linking network, and the resulting hydrogel can still be subjected to subsequent zinc sulfate treatment and device assembly.
[0055] In Example 5, after treatment with 0.5 mol / L zinc sulfate solution, the resulting hydrogel was able to form an ion-conductive sensing layer and produce a recognizable resistance response when subjected to deformation; indicating that even at low zinc sulfate concentrations, zinc ion coordination and the migration of zinc and sulfate ions can still endow the device with ion conductivity and strain sensing functions.
[0056] Comparative Example 1: A biomimetic wearable strain sensor device, the preparation method of which is basically the same as that of Example 1, except that: branched starch and zinc sulfate are not added.
[0057] Comparative Example 2: A biomimetic wearable strain sensor device, the preparation method of which is basically the same as that of Example 1, except that the zinc sulfate soaking step is not performed.
[0058] Examples 2 to 5 are all based on the component system, basic preparation process, and device packaging method of Example 1, with adjustments only made to the mass ratio of polyvinyl alcohol to amylopectin, the number of freeze-thaw cycles, or the concentration of zinc sulfate solution, to illustrate the feasibility of the technical solution of the present invention within the above parameter range. All examples maintain the basic technical route of forming a physical cross-linked structure of the polyvinyl alcohol / amylopectin composite network through freeze-thaw and introducing ionic conductivity through zinc sulfate solution treatment. Example 1, as a representative embodiment, has its mechanical properties, electrical properties, and sensing response performance determined by… Figures 1 to 5 The test results shown are explained below.
[0059] A universal testing machine was used to test the PVA / branched starch / Zn of Example 1. 2+ The hydrogel was subjected to uniaxial cyclic tensile testing at a tensile rate of 80 mm / min. Load-unloading stress-strain curves were recorded at strains of 10%, 25%, 50%, 75%, 100%, and 150%. The results are as follows: Figure 1 As shown. From Figure 1 It can be seen that the PVA-starch-Zn of the present invention 2+ The biomimetic ion-conductive hydrogel combines low modulus similar to skin (soft and conformable under small strain), large deformation capability over a wide range of 150%, and energy dissipation toughness that increases with strain, thus solving the mechanical contradiction of existing conductive hydrogels that are difficult to balance between softness and tensile strength.
[0060] The PVA / branched starch / Zn prepared in Example 1 2+The biomimetic ion-conductive hydrogel, along with pure PVA hydrogel and PVA / branched starch hydrogel as controls, were subjected to electrochemical signal testing. The testing method involved electrochemical impedance spectroscopy (EIS) of each sample using a two-electrode method on an electrochemical workstation, with a frequency range of 0.1 Hz to 100 kHz. Ionic conductivity was calculated based on bulk resistance and sample size. The ionic conductivity of each sample is shown below. Figure 2 As shown in the figure. The results indicate that the conductivity of pure PVA hydrogel is only 0.022 mS·cm. -1 After the addition of amylopectin, its polyhydroxy structure enhances hydration, increasing the conductivity to 0.049 mS·cm. -1 ; After further introducing ZnSO4, Zn 2+ and SO4 2- As charge carriers migrate within the network, the conductivity is significantly increased to 0.111 mS·cm. -1 This verifies that zinc sulfate, as an ion carrier, makes a crucial contribution to the conductivity of the sensing layer.
[0061] The biomimetic wearable strain sensor prepared in Example 1 was subjected to 50 cycles of tensile-recovery testing with a 30% strain applied. The results are as follows: Figure 3 As shown, this result demonstrates that the device exhibits excellent fatigue resistance and long-term stability after undergoing initial network rearrangement.
[0062] Periodically light and heavy presses are applied to the device in Example 1. Figure 4 The graph shows the relative resistance change rate over time for the device in Example 1 under periodic light and heavy pressing conditions. From... Figure 4 It can be seen that the amplitude of ΔR / R0 is approximately 25% under slight pressure and approximately 40% under strong pressure, indicating that the resistance change is positively correlated with the intensity of the external force, and the device has the ability to quantitatively sense different levels of force. The peaks, peak values, and trough values of the two sets of curves are highly consistent, indicating that multiple presses with the same force produce nearly identical resistance responses, and the device output is stable and repeatable. Furthermore, the curve returns to near the zero baseline after each release, indicating that the sensor maintains baseline stability and exhibits minimal signal drift during long-term use.
[0063] Periodic deformation was applied to the device of Example 1. Figure 5 This is the curve showing the relative resistance change rate over time of the device in Example 1 under periodic deformation conditions. If actual test data can be provided, the "periodic deformation" can be changed to represent the actual location and operation. Figure 5 As can be seen, the biomimetic wearable strain sensor of the present invention has four major performance characteristics for practical wearable use: high sensitivity, large range, high repeatability and low drift, which meet the needs of human-computer interaction scenarios such as gesture recognition and remote control.
[0064] The device in Example 1 is used as a gesture input unit to collect signals caused by human hand movements and to drive the bionic robotic hand. Figure 6 The demonstration results for six representative gesture states are shown. The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A biomimetic wearable strain sensor device, characterized in that, The device includes a biomimetic ion-conductive hydrogel sensing layer, electrodes disposed at both ends of the biomimetic ion-conductive hydrogel sensing layer, and an elastomer encapsulation layer covering the outside of the biomimetic ion-conductive hydrogel sensing layer and the electrodes. The raw materials of the biomimetic ion-conductive sensing layer include polyvinyl alcohol, amylopectin, zinc sulfate, and water. The biomimetic ion-conductive hydrogel sensing layer is prepared by ion crosslinking a hydrogel formed by polyvinyl alcohol, amylopectin, and water through freeze-thaw cycles into a zinc sulfate solution.
2. The biomimetic wearable strain sensor device according to claim 1, characterized in that, In the biomimetic ion-conductive hydrogel sensing layer, the mass ratio of polyvinyl alcohol to amylopectin is (3~6):(1~3); the total mass of polyvinyl alcohol and amylopectin accounts for 10%~12.5% of the total mass of polyvinyl alcohol, amylopectin and water.
3. The biomimetic wearable strain sensor device for human-computer interaction applications according to claim 1, characterized in that, The concentration of the zinc sulfate solution is 0.5~2 mol / L.
4. The biomimetic wearable strain sensor device according to claim 1, characterized in that, The degree of polymerization of the polyvinyl alcohol is 1700-1800, and the degree of hydrolysis is 99%; the amylopectin is one or more of corn amylopectin, potato amylopectin, wheat amylopectin, and cassava amylopectin.
5. The biomimetic wearable strain sensor device according to claim 1, characterized in that, The electrodes are copper electrodes, copper foils, or silver wires connected to both ends of the biomimetic ion-conductive hydrogel sensing layer via conductive silver paste.
6. The biomimetic wearable strain sensor device according to claim 1, characterized in that, The elastomeric encapsulation layer is a polydimethylsiloxane film, VHB tape, or Ecoflex silicone rubber film.
7. A method for fabricating a biomimetic wearable strain sensor device as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Add polyvinyl alcohol to water, allow it to swell at room temperature, and then heat and stir at 90~95℃ until completely dissolved to obtain a polyvinyl alcohol solution; S2. Take another branched starch and add it to water, then stir and disperse it at 60°C to obtain a branched starch dispersion; S3. The amylopectin dispersion is mixed with the polyvinyl alcohol solution, and stirred at 90~95°C to fully gelatinize the amylopectin and mix it evenly to obtain a polyvinyl alcohol / amylopectin mixed solution; S4. After degassing the mixed solution, pour it into a polytetrafluoroethylene mold, freeze it at -20°C, thaw it at 20~25°C, and repeat the cycle 2~3 times to obtain polyvinyl alcohol / branched starch hydrogel. S5. The polyvinyl alcohol / branched starch hydrogel is immersed in zinc sulfate solution for ionic crosslinking, and then washed to obtain a biomimetic ion-conductive hydrogel as a sensing layer. S6. Electrodes are connected to both ends of the sensing layer using conductive silver paste, and then encapsulated with an elastomer layer to obtain the biomimetic wearable strain sensor device for human-computer interaction applications.
8. The preparation method according to claim 7, characterized in that, In step S1, the swelling time is 0.5-2 h, and the heating and stirring speed is 200-400 r / min for 2-3 h; in step S2, the stirring and dispersing time is 1-2 h; and in step S3, the gelatinization time is 1-1.5 h.
9. The preparation method according to claim 7, characterized in that, In step S4, the degassing is performed under vacuum at 80-85°C for 30-40 minutes; the freezing time is 12-15 hours, and the thawing time is 8-12 hours; in step S5, the soaking temperature is 20-25°C, and the soaking time is 48-72 hours; the washing is performed by rinsing with deionized water 2-4 times.
10. The application of the biomimetic wearable strain sensor device as described in any one of claims 1-6 in human-computer interaction, characterized in that, The biomimetic wearable strain sensor is attached to the surface of human joints, skin, or muscles to collect human motion signals or physiological signals, and the signals are used for gesture recognition, finger bending monitoring, writing recognition, pulse monitoring, swallowing monitoring, remote robotic arm control, or Morse code communication.